The mechanical properties of moulded and thermoformed denture resins - Baloš, Sebastian (Strojniški vestnik, 2015)
This study describes in detail the mechanical properties of polymethylmethacrylate (PMMA) denture base resins with regard to fabrication procedures, moulding and thermoforming. The investigation included eight specimens of each group of the materials, made separately for each experimental protocol (moulding and thermoforming). Analysis of the mechanical properties of the tested resins was comprised of tensile and 3-point bending strengths, elongation, fracture toughness and micro-hardness tests. Data obtained from the mechanical tests were statistically processed by using one-way analysis of variance (ANOVA) with Tukey's post-hoc test and with the significance level Alpha=0.05. Triplex cold specimens showed the lowest bending strength, fracture toughness and micro-hardness as well the highest standard deviations. Biocryl C in a thermoformed condition exhibited higher tensile and bending strength in comparison to the same material but in the as-received condition (before thermoforming), while the results are opposite for fracture toughness and micro-hardness. Compared to Triplex hot, thermoformed Biocryl C had statistically non-significantly higher values for bending strength and micro-hardness, but significantly lower ones for fracture toughness and tensile strength. In contrast, the lowest dissipation of testing results in all mechanical tests was recorded for Biocryl C fabricated by a thermoforming process, meaning that this material has the highest predictability of the materials tested. The mechanical properties of thermoformed PMMA materials are comparable to cold and hot polymerized PMMA materials. Standard deviations obtained for thermoformed PMMA material are lower than those obtained with cold and hot polymerized PMMA materials.
Keywords: dentalne proteze; mehanske lastnosti; mikrotrdota; natelna trdnost; stabilnost proizvodnje; termoformiranje; zobne smole